2019
DOI: 10.3389/fphar.2019.00560
|View full text |Cite
|
Sign up to set email alerts
|

Enaminone Modulators of Extrasynaptic α4β3δ γ-Aminobutyric AcidA Receptors Reverse Electrographic Status Epilepticus in the Rat After Acute Organophosphorus Poisoning

Abstract: Seizures induced by organophosphorus nerve agent exposure become refractory to treatment with benzodiazepines because these drugs engage synaptic γ-aminobutyric acid-A receptors (GABA A Rs) that rapidly internalize during status epilepticus (SE). Extrasynaptic GABA A Rs, such as those containing α 4 β 3 δ subunits, are a putative pharmacological target to comprehensively manage nerve agent-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Cohorts of eight rats were placed into individual Plexiglas R chambers and connected to an EEG monitoring system (MP160, BIOPAC Systems Inc., Goleta, CA, United States) to enable realtime display of brain activity using AcqKnowledge R 5.0 software. After approximately 30 min of baseline, NA exposure proceeded as previously described and shown in Figure 1 (Althaus et al, 2017;McCarren et al, 2018;Jackson et al, 2019;Johnstone et al, 2019;Barker et al, 2020). The NA used was soman (150 µg/kg s.c.).…”
Section: Nerve Agent Exposurementioning
confidence: 99%
“…Cohorts of eight rats were placed into individual Plexiglas R chambers and connected to an EEG monitoring system (MP160, BIOPAC Systems Inc., Goleta, CA, United States) to enable realtime display of brain activity using AcqKnowledge R 5.0 software. After approximately 30 min of baseline, NA exposure proceeded as previously described and shown in Figure 1 (Althaus et al, 2017;McCarren et al, 2018;Jackson et al, 2019;Johnstone et al, 2019;Barker et al, 2020). The NA used was soman (150 µg/kg s.c.).…”
Section: Nerve Agent Exposurementioning
confidence: 99%
“…In the literature, the introduction of the amide group into β-enaminones structure has been described and have interesting biological properties [33,34]. In Fig.…”
Section: Introductionmentioning
confidence: 99%
“…As part of the CounterACT Neurotherapeutics Screening (CNS) Program, we have previously developed a rat model of delayed treatment of OP-induced SE, using the OP insecticide diisopropyl fluorophosphates (DFP), to screen compounds for efficacy in the termination of seizures and reduction of neuronal death (Pouliot et al, 2016;Johnstone et al, 2019;Spampanato et al, 2019;Barker et al, 2020). These previous studies have demonstrated that delayed treatment with MDZ (including standardof-care antidotes) results in a transient reduction in seizure activity that is also associated with a reduction in neuronal loss; however, the duration and magnitude of seizure suppression and the reduction of neuronal loss were minimal (Spampanato et al, 2019) and could be enhanced by adjunct treatment (Johnstone et al, 2019;Barker et al, 2020). To further validate our model for screening of test compounds, we have tested three adjunct therapies -each with unique mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…To further validate our model for screening of test compounds, we have tested three adjunct therapies -each with unique mechanisms. Three drugs were selected by the NIH CNS Program because (1) they are currently approved for use in humans, (2) they have demonstrated some efficacy in reduction of seizure activity and/or neuronal death in humans All experimental procedures were conducted as similarly described (Johnstone et al, 2019;Spampanato et al, 2019;Barker et al, 2020).…”
Section: Introductionmentioning
confidence: 99%